PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN BOOKLET TERHADAP SIKAP REMAJA PUTRI TENTANG TABLET TAMBAH DARAH DI SMPN 2 BARAMBAITAHUN 2025 - Fitriana, Fitriana; Hipni, Rubiati; Rusmilawaty, Rusmilawaty; Isnaniah, Isnaniah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: The prevalence of anaemia among adolescent girls in the Barambai Public Health Centre’s working area has decreased. However, a preliminary study at Barambai 2 State Junior High School, which has the highest number of cases, found that 90% of students had limited knowledge of iron and folic acid supplements (IFAS), and 69% of that group experienced anaemia. The majority of students also did not consume IFAS regularly. Objective: This study aims to examine the effect of health education using booklets on female adolescents’ attitudes towards iron supplement tablets at SMPN 2 Barambai in 2025. Methods: This study employed a pre-experimental design with a one-group pre- test and post-test approach. A total of 30 adolescent girls were selected using simple random sampling. Data on attitudes towards TTD were collected using a structured questionnaire before and after the intervention. Statistical analysis was conducted using the Wilcoxon test. Results: Out of 30 participants, 19 (63.3%) exhibited a positive attitude before the booklet intervention, and this increased to 22 (73.3%) after the intervention. Meanwhile, 11 participants (36.7%) initially showed a negative attitude, which decreased to 8 (26.7%) post-intervention. These findings indicate a significant change in the participants’ attitudes following the booklet distribution. Conclusion: Health education using a booklet has a positive influence on the attitudes of adolescent girls regarding iron supplementation at SMPN 2 Barambai.